2015
DOI: 10.18632/oncotarget.6357
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of oxidative phosphorylation in the liver by expression of the ATPase inhibitory factor 1 induces a tumor-promoter metabolic state

Abstract: The ATPase Inhibitory Factor 1 (IF1) is an inhibitor of the mitochondrial H+-ATP synthase that regulates the activity of both oxidative phosphorylation (OXPHOS) and cell death. Here, we have developed transgenic Tet-On and Tet-Off mice that express a mutant active form of hIF1 in the hepatocytes to restrain OXPHOS in the liver to investigate the relevance of mitochondrial activity in hepatocarcinogenesis. The expression of hIF1 promotes the inhibition of OXPHOS in both Tet-On and Tet-Off mouse models and induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
132
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(148 citation statements)
references
References 58 publications
16
132
0
Order By: Relevance
“…Permeabilised skeletal muscle tissue (electron transport chain [ETC] complexes) or isolated mitochondria (H + -ATP synthase) were used for the spectrophotometric determination of activities [7, 21]. See ESM Methods: Determination of the activity of OXPHOS complexes and Mitochondria isolation and H + -ATP synthase activity.…”
Section: Methodsmentioning
confidence: 99%
“…Permeabilised skeletal muscle tissue (electron transport chain [ETC] complexes) or isolated mitochondria (H + -ATP synthase) were used for the spectrophotometric determination of activities [7, 21]. See ESM Methods: Determination of the activity of OXPHOS complexes and Mitochondria isolation and H + -ATP synthase activity.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the overexpression of IF1 in colon cancer cells triggers the transcriptional activation of the NF-κB pathway, thereby favoring proliferation and preventing cell death (27). Similarly, less apoptosis and an enhanced proliferation have been observed in induced hepatocarcinomas in transgenic mice overexpressing a constitutively active mutant of IF1 (46). Prevention of cell death by the overexpression of IF1 has also been observed in lung (21) and gastric (31) cancer cells.…”
Section: Discussionmentioning
confidence: 93%
“…Herein, we report that the overexpression of IF1 in human breast carcinomas, especially in the subgroup of triple-negative breast carcinomas predicts a lower risk for metastatic disease (21). This finding is counterintuitive since (i) the overexpression of IF1 inhibits mitochondrial respiration and enhances glycolysis, which is a metabolic phenotype that is enforced in proliferating invasive cells (2, 3, 5, 6), (ii) a high expression level of IF1 has been recently reported as biomarker of bad prognosis in human hepatocarcinomas (28) and in carcinomas of the lung (29), bladder (30), and stomach (31) and in gliomas (32), and (iii) the overexpression of IF1 in the liver of transgenic mice significantly contributes to an increase in hepatocarcinogenesis (46). To investigate the molecular mechanisms that might support the “non-canonical” behavior of IF1 in breast cancer, which might open up potential new trends in diagnosis and treatment of breast cancer patients, we developed the triple-negative breast cancer BT549-luc cell line that stably overexpresses IF1.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, inhibition of the H + -ATP synthase activity has been reported by the overexpression of IF1 or its constitutively active mutant H49K in cells in culture [57, 82, 83] and in neurons [58] and in hepatocytes [42] of transgenic mice in vivo. Consistently, it has been reported that IF1 inhibits the translocation of protons mediated by the H + -ATP synthase when operating in synthetic and hydrolytic modes [84] (Fig.…”
Section: The Atpase Inhibitory Factor 1 (If1): a Master Regulator Of mentioning
confidence: 99%